2020
DOI: 10.3390/ani10081283
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Mannan Oligosaccharides Modulate Gut Inflammatory Response and Improve Duodenal Villi Height in Post-Weaning Piglets Improving Feed Efficiency

Abstract: The aim of this study was to evaluate the effects of mannan oligosaccharides (MOS) on gut health and performance in post-weaning piglets. In total, 40 piglets were divided into two experimental groups and fed a basal diet with (TRT) or without (CON) 0.2% mannan oligosaccharides for 35 days. Growth performance was determined weekly and faecal microbial composition on days 0, 14 and 35. On day 36, histometrical evaluations were performed on duodenal, jejunal, ileal, and colon samples. mRNA gene expression of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 51 publications
(85 reference statements)
0
19
1
Order By: Relevance
“…The number of pigs used in each group (n 8) meets this minimal requirement of statistic for digestible trials or mechanism studies (e.g. six replicates are acceptable) (21,22) . Pigs received the same parental nutrition and management (e.g.…”
Section: Animal Diets and Experimental Designmentioning
confidence: 99%
“…The number of pigs used in each group (n 8) meets this minimal requirement of statistic for digestible trials or mechanism studies (e.g. six replicates are acceptable) (21,22) . Pigs received the same parental nutrition and management (e.g.…”
Section: Animal Diets and Experimental Designmentioning
confidence: 99%
“…Similar effects were noted for piglets when the pregnant and lactating sows received inulin (Paßlack et al, 2015;McCormack et al, 2019;Li et al, 2020). Many studies Castillo et al, 2008;Agazzi et al, 2020;Zhou et al, 2020) focused on the effect of mannooligosaccharides (MOS) as an additive to feed for piglets at weaning age.…”
Section: Organic Acids/preservativesmentioning
confidence: 80%
“…For neonatal mammals including the pigs, disruption of the intestinal epithelium usually leads to altering intestinal permeability, facilitating the invasion of enteric pathogenic bacteria, and triggering intestinal in ammatory response [28][29][30]. MOS is a nondigestible oligosaccharide that has been reported to improve the growth performance and intestinal health due to its prebiotic effects [18,20]. In the present study, we investigated the potential of MOS against in ammation and disruption of the intestinal epithelium in weaned pigs exposure to ETEC.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, MOS was found to enhance the growth performance and attenuate the gastrointestinal in ammatory response in weaned pigs and other animal species [17][18][19]. Although, a number of studies indicated a bene cial effect of MOS on growth performance and gut health in animals [17,20,21], the mechanisms of action of MOS is just beginning to be explored.…”
Section: Introductionmentioning
confidence: 99%